Morphology-controlled synthesis and field-emission properties of patterned SnO2 nanostructures with different morphologies. Issue 8 (1st June 2017) - Ma, L.A.; Wei, Z.H.; Ye, X.Y.; Lin, J.Y.; Hu, L.Q.; Guo, T.L.
Abstract: Tin oxide nanostructured arrays with different morphologies were grown on stainless-steel mesh substrates by a simple thermal evaporation process. It was found that the SnO2 nanostructures could be easily changed from nanobelts to nanocones, nanoneedles, micro-rods, ultra-long nanowires, and slim nanorods by controlling the parameters of growth temperature and N2 /O2 flow. A model combining vapor-liquid-solid (VLS)-base growth and vapor-solid (VS)-tip growth was proposed to explain the growth of SnO2 nanostructures with manifold morphologies. Field-emission (FE) studies revealed that the morphologies of these patterned SnO2 nanostructures had considerable effects on the FE properties. Among these nanostructures, ultra-long nanowire arrays had the lowest turn-on field (~0.47 V/um) and the highest field enhancement factor (~8848). More importantly, the ultra-long nanowire emitters showed excellent FE stability with fluctuations within 2.7%. The enhanced FE properties may be attributed to synergic effects arising from the aligned structures of the ultra-long nanowire emitters, their smaller areal density and their highest aspect ratio (~12000).